Contemporary Approaches to Public Policy
XV, 206 p. 5 illus., 3 illus. in color.
Keywords: This book considers a range of contemporary approaches to public policy studies. These approaches are based on a number of theoretical perspectives on decision-making, as well as alternative perspectives on policy instruments and implementation. The range of approaches covered in the volume includes punctuated equilibrium models, the advocacy-coalition framework, multiple streams approaches, institutional analyses, constructivist approaches, behavioural models, and the use of instruments as an approach to public policy. The volume concludes with a discussion of fundamental issues of democracy in public policy. B. Guy Peters is Maurice Falk Professor of American Government at the University of Pittsburgh, USA, and President of the International Public Policy Association. He was founding co-editor of Governance and of the European Political Science Review, and is the author or editor of over 80 books in political science and public policy. Philippe Zittoun is Research Professor of Political Science and General Secretary of the International Public Policy Association. His last book was The Political Process of Policymaking (Palgrave, 2014). He is on the editorial board of the Policy Studies Journal, Critical Policy Studies, Journal of Policy Research and Policy and Society.